Germany has a high demand in meniscal allograft transplantation but is subject to health economic and legal challenges: a survey of the German Knee Society - Winkler, Philipp W.; Faber, Svea; Balke, Maurice; Metzlaff, Sebastian; Niethammer, Thomas R.; Roessler, Philip P.; Henkelmann, Ralf; Kurme, Alexander; Colcuc, Sebastian; Zimmermann, Gerald; Petersen, Wolf; Diermeier, Theresa A. (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2022)
Purpose To determine the current status and demand of meniscal allograft transplantation (MAT) in Germany among members of the German Knee Society (= Deutsche Kniegesellschaft; DKG). Methods An online survey was conducted between May 2021 and June 2021 and sent to all members of the DKG. The survey questionnaire consisted of 19 questions to determine the demand and technical aspects of MAT among the participants and to identify areas of improvement in MAT in Germany. Results Overall, 152 participants, 136 (89.5%) from Germany, 8 (5.3%) from Switzerland, 6 (4.0%) from Austria, and 2 (1.3%) from other countries completed the online survey, with the majority working in non-academic institutions. According to the regulations of the DKG, 87 (57.2%) participants were board certified as specialized knee surgeons and 97 (63.8%) worked primarily in the field of orthopedic sports medicine. MAT was considered clinically necessary in Germany by 139 (91.5%) participants. Patient age (83.6%), post-meniscectomy syndrome in isolated lateral (79.6%) and medial (71.7%) meniscus deficiency, and functional and athletic demands (43.4%) were the most important determinants to consider MAT in patients. Participants reported that reimbursement (82.9%), jurisdiction over the use of donor grafts (77.6%), and the availability of meniscal allografts (76.3%) are the main challenges in performing MAT in Germany. The most frequently used meniscal allograft types by 54 (35.5%) participants who had already performed MAT were fresh-frozen grafts (56.6%), peracetic acid–ethanol sterilized grafts (35.9%), and cryopreserved grafts (7.6%). Participants reported to perform suture-only fixation more often than bone block fixation for both medial (73.6% vs. 22.6%) and lateral (69.8% vs. 24.5%) MAT. Conclusion More than 90% of the responding members of the DKG indicated that MAT is a clinically important and valuable procedure in Germany. Reimbursement, jurisdiction over the use of donor grafts, and the availability of meniscal allografts should be improved. This survey is intended to support future efforts to facilitate MAT in daily clinical practice in Germany. Level of evidence Level V.